Implementasi Undang-Undang Perlindungan Anak dalam Penanganan Eksploitasi terhadap Anak Jalanan - Andreas Nainggolan; Rahmayanti Rahmayanti; Masitah Pohan (Pusat Riset dan Inovasi Nasional, 2025)
The exploitation of street children is a complex social problem in Indonesia, especially in large cities. Children living on the streets are highly vulnerable to exploitation. Although the government has regulated child protection through Law No. 35 of 2014 as a revision of Law No. 23 of 2002, the implementation of these protections has not been optimal in practice. This study aims to analyze the implementation of the Child Protection Law in addressing the exploitation of street children, identify obstacles in its implementation, and evaluate the suitability of legal norms with their practices. This study uses a normative legal method with a descriptive qualitative approach, based on an analysis of legal documents, scientific literature, and relevant data. The results of the study show that the implementation of child protection still faces many obstacles, such as a lack of supporting facilities, poor coordination between institutions, a lack of education for the community, and weak law enforcement. In addition, there is still a gap between ideal legal provisions and practices in the field. In conclusion, child protection is not sufficient with regulations alone but also requires integrated, sustainable, and participatory implementation so that Indonesian children, especially street children, can live safely, be protected, and develop optimally.